A traceless photocleavable linker for the automated glycan assembly of carbohydrates with free reducing ends. Issue 66 (27th July 2016) - Wilsdorf, M.; Schmidt, D.; Bartetzko, M. P.; Dallabernardina, P.; Schuhmacher, F.; Seeberger, P. H.; Pfrengle, F.
Abstract : A traceless photocleavable linker for automated glycan assembly provides access to complex carbohydrates with free reducing ends, as demonstrated with the successful preparation of nine plant cell wall-related oligosaccharides. Abstract : We report a traceless photocleavable linker for the automated glycan assembly of carbohydrates with free reducing ends. The reductive-labile functionality in the linker tolerates all commonly used reagents and protocols for automated glycan assembly, as demonstrated with the successful preparation of nine plant cell wall-related oligosaccharides, and is cleaved by hydrogenolysis.